Pengaruh Persepsi Manajemen Perubahan Terhadap Kinerja Dokter Dengan Gaya Kepemimpinan Transformasional Dan Resistensi Sebagai Variabel Intervening - R. M, Elvina.; Adhikara, M.F Arrozi; Kusumapradja, Rokiah (Fakultas Ekonomi Universitas Gresik, 2023)
Physician performance cannot be assessed in general because it concerns the patient's clinical outcomes to the services provided. Change management is a strategy used to maintain the position of RS in today's business world, if change management is not prepared and managed properly, it will cause resistance and affect performance, especially if without the support of leaders who have a transformational leadership style. The purpose of this study was to analyze the effect of change management on physician performance mediated by transformational and resistance leadership styles. This study is an explanatory research with a quantitative approach in the form of using hypothetical causality on 62 doctors who worked at least 1 year before change management occurred. The data analysis methods used are the Three Box Method and path analysis. In this study, it was found that the perception of change management has a negative and significant influence on doctor performance, the perception of change management does not have a significant effect on transformational leadership style, the perception of change management has a positive and significant effect on resistance, transformational leadership style has a positive and significant effect on doctor performance, resistance has a positive and significant effect on doctor performance, leadership style Transformational has a positive and significant effect on resistance and the perception of change management has a significant positive effect on clinician performance if mediated by transformational leadership style and resistance as intervening variables.